Portable solar street lamp - Abdullah, Ariffin (2008)
This system is designed for outdoor application in un-electrified remote rural areas. This system is an ideal application for campus and village street lighting. The system is provided with battery storage backup sufficient to operate the light for 10-11 hours daily. The project is about to develop and fabricate the circuit that can charge the lead acid battery during day time by using solar as the source. To control the circuit for charging, I have used the circuit charging that can implement the condition of the charging whether it’s in charging condition of in float condition. When charging condition, red LED will turn on until the battery reach the full charge state that is in floating condition and green LED will turn on. For the switching, I used PIC16F877A to switch on the lamp, by using the photocell sensor. The PIC16F877A will determine whether it is daytime or night time. The light will automatically on when the photocell sensor give the input to the PIC and PIC will give the output to the relay to switch on the light. To control the intensity of the light, we need the other input from the sensor. When sensor detect, PIC will give the output to switch on for the second light. So the intensity of the light will increase and the timing will start counter. After finish the counter, PIC will automatically of the second light. By using this method, its can save the energy that we using from the battery. When night change to the day, photocell sensor detect the ray from the sun, PIC will give the output to off the lamp and the charging circuit will continue charge the battery for the day.